ANALISIS DOKTRIN PIERCING THE CORPORATE VEIL DALAM KERUGIAN PERSEROAN TERBATAS : An Analysis of The Doctrine of Piercing The Corporate Veil in Limited Liability Company Losses - Muhammad Khazas Fadhila Djou; Arif Wicaksana (Faculty of Law, Universitas Trisakti, 2026)
The principle of fiduciary duty constitutes a fundamental obligation that must be upheld by the Board of Directors in managing company, as stipulated in Article 97 paragraphs (2) and (3) of Law Number 40 of 2007 concerning Limited Liability Companies. Directors may be held liable if they are proven to have acted negligently or unlawfully in performing their duties. The problem formulation in this article concerns the liability of the Board of Directors PT Sri Rejeki Isman Tbk, which suffered significant losses due to the misuse of company funds, with focus on the application the doctrine of piercing the corporate veil. This study employs normative legal research method with approach based on legal principles, utilizing secondary data consisting of primary, secondary, and tertiary legal materials, which analyzed qualitatively and concluded deductively. The results and conculicions indicate that the Board of Directors may be held personally liable due to indications of fiduciary duty violations, including the misuse of company funds for personal interests and disregard for the company’s interests. These findings affirm that the doctrine of piercing the corporate veil may be applied to overcome limited liability protection and impose personal liability on the Directors for the losses suffered the company.